1986
DOI: 10.1002/aic.690321022
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of desulfurization in a fluidized‐bed limestone reactor

Abstract: One of the most promising techniques of sulfur dioxide removal from flue gas is sorption using a fluidized bed of limestone. Two commonly considered schemes are the passing of combustion gases through the fluidized bed of limestone or actually burning fuel, e.g., coal, within such a bed (Zielke et al., 1970). Although the latter alternative seems to be more attractive and has been under intensive investigation (Horio and Wen, 1976;Zheng et at., 1982) the former scheme is also desirable since it can be designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…25,64,66,[138][139][140][141][142][143][144][145][146][147][148][149] Shadman and et al 139,[150][151][152] have demonstrated the effectiveness of sorbents (alumina, bauxite, emathlite, kaolinite, silica, limestone) for the capture of lead, cadmium, and other alkali metal vapors. Wu et al 181 extended their earlier studies to the development of a multifunctional sorbent for capture of sulfur dioxide, alkali metals, and lead.…”
Section: Sorbent Methodologiesmentioning
confidence: 99%
“…25,64,66,[138][139][140][141][142][143][144][145][146][147][148][149] Shadman and et al 139,[150][151][152] have demonstrated the effectiveness of sorbents (alumina, bauxite, emathlite, kaolinite, silica, limestone) for the capture of lead, cadmium, and other alkali metal vapors. Wu et al 181 extended their earlier studies to the development of a multifunctional sorbent for capture of sulfur dioxide, alkali metals, and lead.…”
Section: Sorbent Methodologiesmentioning
confidence: 99%
“…The overall coefficient of gas exchange between the bubble and emulsion phase was estimated with the aid of which is often employed in similar systems (Ho et al, 1986; Zheng et al, 1982).…”
Section: Resultsmentioning
confidence: 99%
“…Since the middle of the 1970s, the DAP-desulfurization technique has been intensively studied, both experimentally and numerically. While many comprehensive numerical models for FBC and various gas−solid reaction models for single particles have been set up, comprehensive modeling of DAP on pulverized furnaces, considering most of the influence factors, are rather rarely seen in the literature . Han et al suggested a comprehensive DAP-model for pulverized-coal combustion conditions which includes SO X formation, gas−solid reaction models, the sintering effect on the sorbent, natural retention of coal ash, equilibrium of sulfation, etc.…”
Section: Introductionmentioning
confidence: 99%